When women get involved - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The Ivuso women s group in Makindu in Kenya started out as a literacy and self-help group. As time went by, it developed into a pilot undertaking for promoting improved strains of sorghum and millet, with support from the Kenya Agricultural...